Agro-Economic Performance of Intercropping Hybrid Maize with Vegetables and Spices at Farmer’s Field (Bangladesh Agronomy Journal, 2019)
The experiment was conducted at Multi Location Testing (MLT) site, Moulvibazar, Bangladesh during rabi season of 2016-17 and 2017-18 to study the profitability of intercropping of hybrid maize with vegetables and spices. Five intercrop combinations of hybrid maize along with sole maize were arranged in randomized complete block design (RCBD) replicated six times. There were six treatments viz., T1: Maize + potato, T2: Maize + red amaranth, T3: Maize + spinach, T4: Maize+ data shak, T5: Maize + coriander and T6: Maize as sole. The grain yield of maize in intercropped combination varied significantly. The highest grain yield (9.71 t ha-1) was in sole maize. The highest maize equivalent yield 15.60 t ha-1 was recorded from the treatment T1 (100% maize + potato) whereas the lowest yield (8.61 t ha-1) was obtained from the treatment T6 (sole maize). The highest gross return (Tk. 312000 ha-1) and benefit cost ratio (3.29) was obtained from the treatment T1 (100% maize + potato). On the contrary, the lowest gross margin (Tk. 101600 ha-1) was obtained from treatment T2 (maize + red amaranth). It revealed that the combination of maize with potato was more compatible and profitable intercropping system in Sylhet region of BangladeshBangladesh Agron. J. 2018, 21(2): 73-78